Pengaruh Perilaku Inovatif, Keterlibatan Pegawai dan Modal Intelektual terhadap Kinerja Pegawai di Dinas Pariwisata Kota Padang - Wulandari Septianingsih; Mellyna Eka Yan Fitri (ARZUSIN, 2026)
Although numerous studies have examined employee performance in the public sector, research simultaneously analyzing the effects of innovative behavior, employee engagement, and intellectual capital within the context of local tourism agencies remains limited. This study aimed to analyze the effects of innovative behavior, employee engagement, and intellectual capital on the performance of employees at Dinas Pariwisata Kota Padang. The study employed a quantitative approach with a survey design and involved all 72 employees as respondents, selected using a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression with the assistance of SPSS version 30. The results showed that innovative behavior had a positive but nonsignificant effect on employee performance, whereas employee engagement and intellectual capital had positive and significant effects on employee performance. Simultaneously, innovative behavior, employee engagement, and intellectual capital had a significant effect on employee performance. These findings confirm that enhancing employee engagement and managing intellectual capital are important strategies for improving public-sector employee performance, whereas the implementation of innovative behavior requires organizational support to produce a more optimal impact. This study contributes to enriching the human resource management literature on factors influencing employee performance and provides practical implications for government agencies in designing more effective human resource management policies. Future research may examine the role of other factors, such as leadership and organizational culture, in improving employee performance.